Breast cancer in the 17th century: the cases of the wives of Luis Guillermo de Moncada (1614-1672) - Fornaciari, Antonio; Giuffra, Valentina; Fornaciari, Gino (Medicina Historica, 2023)
The human remains of nobles housed in the Neapolitan Basilica of Saint Domenico Maggiore (15-17th centuries) are an important series with regard to paleo-oncology, since three out of five cases of soft tissue tumours known in paleopathology worldwide are documented in this Italian series. Among the bodies of Saint Domenico Maggiore there are the first and the second wife of the Prince Luis Guillermo de Moncada (1614-1672): Maria Afán de Ribera (ca1615-1639) and Catalina Moncada de Castro (1611-1659). Both women died of breast cancer, as shown by the archival sources. The bodies of the two women are skeletonized and the radiological analysis allowed us to identify some focal osteolytic lesions of neoplastic origin. These cases constitute the first examples of breast cancer diagnoses in ancient human remains supported by the integration of archival sources and paleopathological investigations.These two new cases must be added to the three previously known malignant tumours from San Domenico Maggiore. In this Neapolitan series, out of a total of eighteen adult individuals aged 25-71 years, five (28%) were affected by cancer. Despite the small sample size, this prevalence is surprisingly comparable to that of the contemporary Western world.